2004
DOI: 10.1007/s00066-004-1299-x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Cerebral Metastases from Breast Cancer with Stereotactic Radiosurgery

Abstract: SRS alone is an effective treatment for patients with one to three brain metastases from breast cancer. A randomized trial should be performed to evaluate whether WBRT is a necessary component in the primary treatment of these patients. Salvage SRS is an effective therapy option after WBRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 50 publications
3
49
0
2
Order By: Relevance
“…Many of the lesions slowly decrease in size and dissolve following treatment with gamma-knife SRS [56]. Combs et al [57] studied the impact of WBRT and focal boost SRS versus SRS alone in patients with brain metastases from primary breast cancer. They reported that survival was longer in patients receiving SRS only than in those receiving WBRT plus SRS as a focal boost.…”
Section: Radiosurgerymentioning
confidence: 99%
“…Many of the lesions slowly decrease in size and dissolve following treatment with gamma-knife SRS [56]. Combs et al [57] studied the impact of WBRT and focal boost SRS versus SRS alone in patients with brain metastases from primary breast cancer. They reported that survival was longer in patients receiving SRS only than in those receiving WBRT plus SRS as a focal boost.…”
Section: Radiosurgerymentioning
confidence: 99%
“…Combs et al [ 105 ] do not report any toxicity in 32 GBM treated with 17 Gy. The higher rate of severe effect reported in the fi rst study might be due to the largest treatment volume (28 cm 3 vs. 10.1 and 10 cm 3 ).…”
Section: Radiation Therapymentioning
confidence: 96%
“…A single-institution review of 105 patients with 1-4 brain metastases, however, showed that the addition of WBRT to SRS did not result in improvement in survival or local control if salvage therapy was available for recurrence after SRS alone (Sneed, 1999). This lack of a statistically significant difference in overall survival was confirmed by seven other retrospective cohort studies (Chidel, 2000;Hoffman, 2001;Jawahar, 2002;Noel, 2003;Pirzkall, 1998;Sneed, 2002;Varlotto, 2005) and one prospective cohort study (Li, 2000), while one study showed a survival benefit for SRS alone (Combs, 2004) and another showed a survival benefit for SRS+WBRT (Wang, 2002). Among these 10 retrospective cohort studies, only one reported a statistically significant worsening in local tumor control for patients treated with SRS alone compared to SRS+WBRT (Varlotto, 2005).…”
Section: Omission Of Wbrt From Srs Treatment For Limited Metastasesmentioning
confidence: 96%